Unilateral biportal endoscopic lumbar interbody fusion assisted by a Tianji robot for lumbar degenerative disease in elderly patients: a retrospective study - Guofang Fang; Jin Zhang; Hailun Zhu; Xunwei Lai; Jianchang Wu; Xiuwang Li; Zhouxu Hou; Fangxin Chen; Hongxun Sang (European Journal of Medical Research)
Abstract Background Unilateral biportal endoscopic lumbar interbody fusion (UBE-LIF) has been successfully used to treat degenerative lumbar spinal diseases. Nevertheless, the duration of the UBE-LIF procedure notably exceeds that of minimally invasive transforaminal lumbar interbody fusion (Mis-TLIF), increasing the potential for perioperative complications, particularly in elderly patients. Objective This retrospective study aimed to compare the results of robot assistance (RA) and non-assistance (NA) groups and to explore the benefits of UBE-LIF assisted by a Tianji robot in aged patients. Methods 60 patients were divided into two groups: 30 patients in the RA group and 30 in the NA group from January 2022 to June 2023. The surgical duration, estimated intraoperative blood loss, postoperative drainage, length of hospital stays, and radiation exposure were examined and documented. Clinical assessments, including the Oswestry Disability Index (ODI), visual analog scale (VAS), modified MacNab criteria, postoperative complications, and interbody fusion rate, were also evaluated. Results No significant differences were observed between the two groups in terms of postoperative drainage, length of postoperative hospital stay, or fusion rate. However, the RA group exhibited lower perioperative complications, estimated intraoperative blood loss, and duration of radiation exposure than the NA group. The average total operation time in the RA group was 105.3 ± 25.8 min, which was significantly shorter than the NA group’s average of 130.5 ± 22.5 min (P < 0.001). Furthermore, both groups demonstrated improvements in all clinical outcomes at various postoperative time points, with no significant differences between them (P > 0.05). Conclusions Compared with the NA approach, robot-assisted UBE-LIF technology provides accurate intraoperative guidance and helps spinal surgeons achieve accurate decompression. Furthermore, it can reduce radiation exposure, operation time, blood loss, and surgical complications, thereby improving the surgical efficiency and safety.